BSCI-07. Multiomics characterization of brain metastases in multiple histologies identifies enrichment of oxidative phosphorylation as a promising therapeutic target. (9th August 2021) - Fukumura, Kazutaka; Malgulwar, Prit Benny; Fischer, Grant; Hu, Xiaoding; Zhang, Xiang; Yu, Dihua; Debeb, Bisrat; Davies, Michael; Huse, Jason
Abstract: Purpose: Brain metastasis (BM) is a lethal complication from systematic malignant tumors, and the incidence is approximately 10–30% of patients with advanced cancer. Extensive genomic analyses with large sample sets and the following functional studies revealed clinically relevant characteristics for BMs. However, these studies have not identified specific abnormalities driving BM in multiple tumor histologies yet. To identify molecular pathogenesis and promising therapeutic targets shared across multiple histologies of BMs, we performed multiomics molecular profiling, along with functional studies using in vitro and in vivo BM models. Methods: Frozen tissues of patient-matched BMs and primary tumors (or extracranial metastases) from breast cancer ( N = 14), lung cancer ( N = 14) and renal cell carcinomas ( N = 7) patients were carried out whole-exome sequencing, mRNA-Seq and reverse-phase protein array. Paired parental and brain metastatic derivatives of MDA-MB-231 and BT474 were examined to assess findings from the multiomics datasets. SCID/beige mice were inoculated with MDA-IBC3 cells via tail vein injection and administered an oxidative phosphorylation (OXPHOS) inhibitor by oral gavage daily for 96 days. Results: The multiomics molecular profiling identified enrichment of OXPHOS shared across the histologies of BMs. Brain metastatic derivative cell lines also demonstrated enhanced oxidative metabolism, along with the sensitivity to an OXPHOS inhibitor. Moreover, in vivo studies revealed that OXPHOS inhibition significantly impaired the formation of BM, and fresh brain metastatic derivatives from the murine BM model exhibited the higher oxidative metabolism and sensitivity to the OXPHOS inhibitor as with the prior in vitro studies. Conclusions: Our multiomics characterization of BMs demonstrates heightened oxidative metabolism shared across the multiple histologies, and the OXPHOS inhibition affects more effectively for brain metastatic derivatives rather than the parentals. Further investigation focusing on metabolic abnormalities in BM will likely develop promising therapeutic strategies against BMs.